Quantification of On-Duty Workload in Active-Duty Firefighters - (:unkn) unknown (My University, 2023)
Firefighters are at an elevated risk of musculoskeletal and cardiovascular injury driven by over-exertion. To date, workload in the fire service is quantified as the call volume of a 24-hour shift. However, call volume does not account for the individual demands of different call types (i.e., medical vs. fire emergency), nor does it account for the influence of individual differences on responses to job demands. Sport-athlete populations have utilized traditional external (i.e., stimulus) and internal (i.e., response) training load measures to quantify task workload and inform injury-prevention strategies, however, minimal use of such measures have been utilized in an on-duty setting in the fire service. Therefore, the purpose of this dissertation research was to quantify on-duty workload in the fire service and specifically: (a) examine for differences in workload across emergency call types, (b) examine the influence of a fire suppression and/or auto-extrication call on the load of a 24-hour shift, and (c) identify predictors of workload, including measures of health and fitness and established workload (i.e., call volume) factors. Accordingly, 38 active-duty firefighters were recruited to participate in this two-phase study. Phase 1 included a laboratory session to quantify participant health and fitness characteristics, including peak aerobic capacity, body mass index, and waist circumference. Following, participants completed Phase 2 on-duty data collection to quantify workload of individual medical (MED) and fire calls with (FIRE1) and without (FIRE0) fire suppression and/or auto-extrication, as well as for 24-hour shifts. External workload was quantified as Impulse Load (IMPULSE) and internal workload was quantified physiologically as Edward’s Training Impulse (eTRIMP), perceptually as Foster’s Session Rating of Perceived Exertion (sRPE), and overall using the National Aeronautics and Space Administration-Task Load Index (NASA-TLX). The results indicated that FIRE1 calls have significantly greater IMPULSE, eTRIMP, sRPE, and NASA-TLX workloads than MED and FIRE0. Additionally, the response to at least one FIRE1 call across a 24-hour shift significantly increases the IMPULSE, eTRIMP, sRPE, and NASA-TLX workloads of the shift compared to 24-hour shifts with similar call volumes. Upon examining for workload predictors, total call volume of a 24-hour shift is a significant predictor of the objective work (i.e., IMPULSE) completed across that shift but remains uninfluenced by aerobic capacity or obesity status. The physiological workload (i.e., eTRIMP) of a 24-hour shift is predicted by FIRE1 call volume, as well as aerobic capacity, suggesting that individuals with lower oxygen consumption efficiencies will accumulate greater physiological workloads across a shift. The perceived workload (i.e., sRPE) is also significantly predicted specifically by the volume of FIRE1 calls. Finally, the NASA-TLX as an overall workload measure is unrelated to both measures of call volume, nor the examined measures of health and fitness. Collectively, these results suggest that preparation and recovery strategies may need to specifically target firefighters with exposure to fire suppression and/or auto-extrication calls, including unique call and shift strategies. Additionally, due the influence of aerobic capacity on the physiological workload of 24-hour shifts, targeted strategies to enhance aerobic capacity may decrease the workload response across a shift and support exertion-driven injury mitigation.
Keywords: aerobic capacity; call volume; fire suppression; firefighter; job demands; workload